Managing Positions in a Dynamic Environment - New Technology Impact on Tactel and the Telecom Industry - Arvinius,Fredric; Halvarsson,Daniel (2006)
The Telecom industry is facing a paradigm shift, where the industry is converging with Internet technologies and the market is becoming more sophisticated. This results in more demanding customers, and the need for offering more content and services with a focus on usability for the end-users. The operators are starting to loose both their strong position and revenue in the Telecom industry, due to new technology and the fact that other actors are starting to enter the market, offering new content and services. In the end, the operators have two choices, to become bit-pipe providers, and only focusing on network management, or keeping the control over their networks. The latter would mean that they block other actors who are taking parts of their revenue, e.g. Skype who are their biggest threat when it comes to voice. With IMS, being a centralised architecture, operators hope to keep their strong position in the network, and increase their overall revenue. Several operators and network vendors have already started to implement IMS. However, the “Big Network” that the industry is talking about, is questionable. First of all, this would require large investments from the operators, who already have weak financial statements from their current network infrastructure investments. Secondly, all operators have to join IMS to really get the most out of the network, and finally, it takes up to five years to fully implement. In addition to the IMS impact, Skype will keep experience a constant growth, since the network is becoming more and more IP based. Skype will particularly flourish when flat-rates are released by the operators, which is just a matter of time. For smaller companies, such as Tactel, this paradigm shift makes their position and relationships even more important. In this case, Tactel should focus on building partnerships with equal actors, companies with the same technical interest or customers, and opt for bigger customers. Moreover, they should invest to some extent in in-house expertise regarding IMS, and find relationships with actors who have a broader knowledge of IMS to complement Tactel’s competence. This way, they do not have to tie up too much of their resources in the beginning, especially since they are not first movers and IMS’ role is still uncertain. Finally, they should try to find a niche in the range of their competences, which they can prosper from.
Keywords: Telecom industry; IMS; Skype; Industrial Network; Structural Hole; Technology Life-Cycle; Position; Relationship; Management of enterprises; Företagsledning, management